Interactions of vanadates with carbohydrates in aqueous solutions - Ribeiro, Ana C. F. (2004)
The interaction between the vanadate ion (VO3-, i.e. vanadium (V)) and the carbohydrates sucrose, glucose and fructose has been studied in aqueous solutions (pH [approximate]6, 298.15 K) using measurements of diffusion coefficients, electrical conductivity, Raman and multinuclear NMR spectroscopy. With sucrose and glucose, indications of hydrolysis of the anion in the absence of the sugars came from a decrease in the diffusion coefficient with increasing concentration. Significant effects on the diffusion coefficients were observed in the presence of sucrose and glucose, suggesting interactions between the carbohydrates and vanadate ion. Support for this came from electrical conductivity measurements, where there were indications of formation of oligomeric species. These were found to depend on the carbohydrate used: confirmation of oligomer formation came from Raman spectroscopy, where it was possible to identify these species, and see their dependence on the particular carbohydrate used. Information on the interactions between the carbohydrates glucose or sucrose and vanadate came from 51V and 1H NMR spectroscopy, where the dominant species appeared to be a 2:2 complex with glucose, possessing trigonal bipyramidal centres, whereas with sucrose it is suggested that octahedral species are formed. Studies with fructose were complicated by competing oxidation of this carbohydrate and reduction of vanadium (V).